Effect of egualen sodium hydrate on small-intestinal mucosal damage induced by low-dose aspirin: a prospective randomized clinical trial - Iguchi, Munetaka (J Clin Biochem Nutr, 2018)
Low-dose aspirin, which is widely used to reduce the risk of cardio- and cerebrovascular thrombosis, often induces gastroenteropathy by increasing the permeability of the mucosa. However, therapeutic strategies for patients with low-dose aspirin-induced small intestinal injury have not been determined. We evaluated the preventative effect of egualen sodium hydrate, a gastro-protective agent that suppresses indomethacin-induced small-intestinal damage in rats, against small-intestinal mucosal damage induced by low-dose aspirin in healthy adult male volunteers. Participants were randomly allocated to receive aspirin 100 mg/kg daily (control group, n = 10) or aspirin 100 mg/kg plus egualen sodium 30 mg daily (egualen sodium group, n = 10). Small intestinal mucosal injury was evaluated by capsule endoscopy two weeks after initiation of drug administration. Fecal analyses (occult blood test, immunochemical test, transferrin measurement and calprotectin measurement) were carried out before and after treatment. Egualen sodium significantly suppressed the total number of small intestinal injuries detected by capsule endoscopy and the positive ratio for the fecal occult blood test. Daily use of 30 mg of egualen sodium showed a preventative effect on low-dose aspirin-induced small intestinal injury. Since acid suppression therapy was reported to exacerbate NSAIDs-induced enteropathy via dysbiosis, egualen sodium may be useful for patients treated with low-dose aspirin.